Dynamic connection provisioning in fiber-wireless access networks using tuning-based roadms - Anyuo, Shadrack Omondi (2010)
There has been a continuous demand for broadband services in the recent past majorly attributed to the fall in pricing of high end devices with broadband capabilities. This has brought challenges to network operators since the offered bandwidths need to match the ever increasing demand. While there has been solution for transport network to carry huge traffics through fiber optics technology, access networks have not been able to deliver this huge bandwidth to the end users. More recently, a new powerful access solution, combining the strength of both optical and wireless technologies, is under strong research. This hybrid fiber-wireless (FiWi) access solution is expected to become a powerful platform for the support of future applications and services. In this thesis, dynamic connection provisioning in FiWi access networks is discussed. In order to reduce the overall network costs in the access networks, the use of tunable reconfigurable add/drop optical multiplexers (ROADMs) at the wireless-optical interface is proposed. To achieve dynamic connection provisioning, a heuristic is proposed that minimizes the overall connection blocking probability through efficient routing & wavelength assignment and tuningbased head re-positioning at ROADMs.